I was taught in class that if g(x) is f^-1(x), then g'(y)=1/f'(x)(adsbygoogle = window.adsbygoogle || []).push({});

my notes for an example:

f(x)=x^2

g(x)=f^-1(x)=x^(.5)

g’(4)=?

g(x)= x^(.5)

g’(x)=.5x^-.5

g’(4)=1/f’(x), x=4^(.5)

g’(4)=1/f'(2)=1/2*2=1/4

I have no clue how g(x)=f^-1(x)=x^(.5) and how g’(4)=1/f'(2)

I am just overall confused any help would be appreciated

**Physics Forums | Science Articles, Homework Help, Discussion**

Dismiss Notice

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# Homework Help: Derivative of Inverse

**Physics Forums | Science Articles, Homework Help, Discussion**